Students' Psychological State Degree and Their Speaking Ability: To What Extent is the Link? - Sri Rejeki Murtiningsih; Faradilla Mutiara Islami Darmanto; Sibakhul Milad Malik Hidayatulloh (VELES Voices of English Language Education Society, 2023)
Effective communication among students is often hindered by various obstacles, including reticence, self-doubt, inadequacy, apathy, fear of making mistakes, and apprehension. These challenges are notably evident in their speaking skills. This study aimed to explore the psychological conditions of students from the English Language Education Department (ELED) and relate these conditions to their speaking abilities. A quantitative approach was adopted, using an explanatory correlation design. Data was gathered from 117 third-year students at a private university using a survey and a written assessment. Results showed students' mental well-being was categorized as poor with a mean score of M=45.03. Contrastingly, their speaking proficiency was rated excellent, with a mean score of M=64.24 on the Pearson scale. Correlation analysis was applied to determine the relationship between the two variables. The results yielded a p-value of 0.001, below the 0.05 threshold, thus accepting the alternative hypothesis (H1). A significant relationship between the students' psychological states and speaking abilities was established.